Serway's principles of physics : a calculus-based text. - Jewett, John W. 4 0 16; Serway, Raymond A.; 5 (Australia : Thomson Brooks/Cole, 2006)
Features a concise approach to traditional topics, an early introduction to modern physics, integration of physics education research pedagogies, as well as the integration of contemporary topics throughout the text.
Includes index.
Keywords: 2 -- 0; 6; Physics. -- 20; 20; 2